2008
DOI: 10.1111/j.1523-1739.2008.00920.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Forest Fragmentation and Habitat Degradation on West African Leaf‐Litter Frogs

Abstract: Habitat degradation alters the dynamics and composition of anuran assemblages in tropicalforests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 35 publications
5
65
0
2
Order By: Relevance
“…From western Ivorian forests it has been shown that logging has a serious effect on the composition of frog assemblages. Many forest specialists seem to be unable to prevail in degraded forests, most probably due to an altered microclimate with which they cannot cope , Ernst and Rödel 2006, Hillers et al 2008. Hence, exploring more of the potentially pristine areas in the southern parts of TESF is needed to get a complete impression concerning the presumed original anuran composition in TESF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From western Ivorian forests it has been shown that logging has a serious effect on the composition of frog assemblages. Many forest specialists seem to be unable to prevail in degraded forests, most probably due to an altered microclimate with which they cannot cope , Ernst and Rödel 2006, Hillers et al 2008. Hence, exploring more of the potentially pristine areas in the southern parts of TESF is needed to get a complete impression concerning the presumed original anuran composition in TESF.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of amphibian assemblages thus may reflect the degree of habitat degradation and destruction (for Ivorian examples compare e.g. Ernst and Rödel 2005, Ernst et al 2006, Hillers et al 2008. Hence, conservation recommendations could be based on the presence or absence of particular amphibian species and their continued monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Amphibians, and especially frogs, are of interest in this context for two reasons: (1) the majority of species are dimorphic, with females typically being larger than males (Monnet and Cherry, 2002) and (2) amphibians are characterized by a low overall mobility, making them especially vulnerable to local habitat destruction and habitat fragmentation (Hillers et al, 2008). Thus, dispersal is likely under strong selection in fragmented habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have showed synergies between extreme pH levels (Pahkala et al 2002) or depth of breeding ponds (Kiesecker et al 2001) and excessive ultraviolet exposure, and between the use of pesticides and the presence of predators (Relyea and Mills 2001). Additionally, habitat loss is a major driver of population declines (Beebee and Griffiths 2005, Cushman 2006, Halliday 2008, Hillers et al 2008, Angelone and Holderegger 2009, and the fungus, Batrachochytrium dendrobatidis, has been identified as cause of population declines and extinctions of many species worldwide (e.g., Rohr and Raffel 2010). On the other hand, the effects of climate as a direct driver of extinctions are less clear (e.g., Carey andAlexander 2003, Minter 2011).…”
Section: Introductionmentioning
confidence: 99%